PENGARUH CITRA MEREK DAN HARGA TERHADAP LOYALITAS PELANGGAN AIR MINUM DALAM KEMASAN - Hengestu, Nelsen; Iskandar, Donant Alananto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The purpose of this research is to understand the influence of brand image and price towards mineral water customer loyalty. This research is a quantitative research by using the SPSS Statistic 13 with 114 respondent of the sample which is the people of Medan Satria districts who has to consume Aqua mineral water more than three times in a week using nonprobability sampling method and convenience sampling techniques. The result of this research shows all the three hypothesis in this research are accepted, by partially and together with the coefficient of regression of brand image is 0,275 and price is 0,391. The benefit of this research for Aqua is to give them some suggestion to maintain and enhance the brand image and keeping their price position in order to maintain their position as a market leader in mineral water business Keywords: brand image, price, loyalty